Whole-Exome Sequencing in Searching for New Variants Associated With the Development of Parkinson’s Disease - Shulskaya, Marina V.; Alieva, Anelya Kh.; Vlasov, Ivan N.; Zyrin, Vladimir V.; Fedotova, Ekaterina Yu.; Abramycheva, Natalia Yu.; Usenko, Tatiana S.; Yakimovsky, Andrei F.; Emelyanov, Anton K.; Pchelina, Sofya N.; Illarioshkin, Sergei N.; Slominsky, Petr A.; et al. (Frontiers in Aging Neuroscience, 2018)
Background: Parkinson’s disease (PD) is a complex disease with its monogenic forms accounting for less than 10% of all cases. Whole-exome sequencing (WES) technology has been used successfully to find mutations in large families. However, because of the late onset of the disease, only small families and unrelated patients are usually available. WES conducted in such cases yields in a large number of candidate variants. There are currently a number of imperfect software tools that allow the pathogenicity of variants to be evaluated. Objectives: We analyzed 48 unrelated patients with an alleged autosomal dominant familial form of PD using WES and developed a strategy for selecting potential pathogenetically significant variants using almost all available bioinformatics resources for the analysis of exonic areas. Methods: DNA sequencing of 48 patients with excluded frequent mutations was performed using an Illumina HiSeq 2500 platform. The possible pathogenetic significance of identified variants and their involvement in the pathogenesis of PD was assessed using SNP and Variation Suite (SVS), Combined Annotation Dependent Depletion (CADD) and Rare Exome Variant Ensemble Learner (REVEL) software. Functional evaluation was performed using the Pathway Studio database. Results: A significant reduction in the search range from 7082 to 25 variants in 23 genes associated with PD or neuronal function was achieved. Eight (FXN, MFN2, MYOC, NPC1, PSEN1, RET, SCN3A and SPG7) were the most significant. Conclusions: The multistep approach developed made it possible to conduct an effective search for potential pathogenetically significant variants, presumably involved in the pathogenesis of PD. The data obtained need to be further verified experimentally.